Stability of psychological wellbeing during the COVID-19 pandemic among people with an anthroposophical worldview: the influence of wondering awe and perception of nature as resources - Steinhausen-Wachowsky, Anna; Martin, David; Rodrigues Recchia, Daniela; Büssing, Arndt (Frontiers in Public Health, 2023)
(1) Background: During the COVID-19 pandemic, differences in responses and behaviors were observed among specific groups. We aimed to address how people with an anthroposophical worldview behaved with respect to perception of burden, fears and wellbeing. As it is integral part of their life style and convictions, we addressed the influence wondering awe and gratitude and perception of nature and times of mindful quietness as resources to cope. (2) Methods: In two cross-sectional surveys with standardized instruments, participants were recruited in 2020 (n=1,252) and 2021 (n=2,273); (3) Results: Psychological wellbeing was much higher than in other studied groups and populations, with slightly lower scores in 2021 (Eta2=0.020), while the per-ception of COVID-19 related burden and fear of the future were low in 2020 with a slight increase in 2021 (Eta2=0.033 and 0.008, respectively). Their transcendence conviction was negatively related to fears of own infection or infection of others. Best predictors of their wellbeing was low burden and awe/gratitude, while best predictors of their burden were low wellbeing and lack of social contacts. (4) Conclusions: Compared to the general population in Germany, the anthroposophical lifestyle and related convictions seem to make them more robust against the COVID-19 related burden and helped them to stabilize their psychological wellbeing.